To become Model Pendekatan Komponen Pariwisata 6A Di Desa Mondoluku Menuju Desa Wisata - Rahayu Antasari; Andri Krisna Dianto; Ardiansyah Hendra Lukmana; Longinus Lozha (BRILIANT: Jurnal Riset dan Konseptual, 2025)
To become a tourist village, Mondoluku Village has a diversity of potential that has not been managed optimally, so it is necessary to carry out an analysis using the 6A tourism component model, namely Attraction, Accessibilities, Amenities, Accommodation, Activity and Ancillary Service as a model for the development and development of the Mondoluku tourist village. Readiness of Mondoluku village with analysis of the 6A tourism component approach model, as a model for managing and developing tourism in Mondoluku Village, so that visitors or tourists can enjoy the tourism potential that exists in Mondoluku Village, and it is hoped that it can provide opportunities for the community to take advantage of the potential. exists to support the sustainability of tourism activities.  The research objective is to analyze the 6A tourism component approach model and analyze the supporting and inhibiting factors in developing a tourist village in Mondoluku Village towards a tourist village. This type of research is descriptive qualitative with data collection techniques using observation, interviews and documentation. The results of the research show that tourism development in Mondoluku Village is still not optimal, there is still something that needs to be improved in each component of tourism in every potential tourist attraction in Mondoluku Village.